Demographic processes in forest trees in the Rocky Mountains - Buechling, Arne, author; Martin, Patrick H., advisor; Bauerle, Bill, committee member; Brown, Peter M., committee member; Cheng, Tony, committee member (Colorado State University. Libraries, 2017)
Forests provide numerous ecological and economic services including regulation of biogeochemical cycles, fiber production, watershed protection, as well as less tangible aesthetic and recreational benefits. Forests are being substantially altered by a range of consumptive uses related to expanding human population and economies. Superimposed on other anthropogenic impacts is global climate change. Global circulation models unambiguously reveal the role of greenhouse gas forcings associated with industrial processes in driving global temperature trends (Hanson et al. 2005). Meteorological observations indicate that global mean temperature has increased by approximately 0.6 C over the past century relative to a base 1951 to 1980 period, with record high temperatures occurring in 2010. Paleoclimatic reconstructions based on proxy data indicate that modern rates of warming may be unprecedented in the context of the past 1000 years. Rates of warming are geographically heterogeneous. Temperature anomalies in the Rocky Mountain ecoregion, for example, are 2‒3 times higher than the global mean temperature increase. Some models and observational data suggest that temperature trends are elevation dependent with greater warming at high altitudes and with greater increases in daily minimum temperatures than maximum temperatures. Documented increases in minimum temperature is associated with earlier spring thaw events, driven by minimum temperatures that exceed 0 °C and a lengthening of the growing and fire seasons. In the Rocky Mountains, an altered climate system is projected to result in a higher frequency and intensity of drought events. Precipitation over the previous 100 years lacks clear trends across the region as a whole, but models of snow water equivalent (SWE) indicate declining moisture availability since the mid-20th century. Early spring snowmelt and warming driven increases in rates of evapotranspiration may correlate with reduced stream flow and declines in effective soil moisture late in the growing season. Warming temperatures and reductions in moisture availability have been associated with significant increases in area burned by wildfire in some forest systems, particularly at high elevations where climate variability rather than fuel conditions is the primary driver of fire activity. Changing climate may also be expanding the ranges and altering the dynamics of forest insects, such as the mountain pine beetle (Dendroctonus ponderosae), resulting in extensive tree mortality. The recent widespread acceptance of climate change has highlighted the need for regional and species specific adaptation strategies. However, a lack of reliable projections describing the responses of organisms and communities to climate change has been identified as a major impediment to the development and implementation of climate adaptation strategies within federal agencies. Potential vegetation responses include migration to track preferred habitats or adaptation through phenotypic or genetic plasticity. Heat stress and prolonged drought have been associated with rapid shifts in the range limits of ponderosa pine (Pinus ponderosa) and in significantly elevated rates of background tree mortality for tree species and forest environments worldwide. Mortality events associated with physiological stress or environmental disturbances may accelerate changes in the distributions of long-lived tree species that might otherwise persist in sub-optimal environments. The distribution and abundance of plants are largely determined by physiological, life history, and ecosystem processes, and how these processes interact or respond to climate. A mechanistic understanding of these processes and their physiological thresholds is required to accurately predict forest response to climate change. The 2007 Intergovernmental Panel on Climate Change working group has argued that current predictive vegetation models are limited by a failure to adequately quantify relationships between climate, critical life history processes, and disturbance regimes. The main objective of this research is to quantify life history processes for select tree species in the Rocky Mountain ecoregion. Specifically, non-linear regression models will be developed to quantify variation in both tree fecundity and growth as a function of climate variables, edaphic gradients, and competition. Comprehensive field data will be used to train flexible functions in a maximum likelihood framework. Competing models representing alternative hypotheses will be evaluated using information theory. The overarching objective of this project is to provide detailed quantitative life history information that may subsequently be used to parameterize dynamic simulation models for the prediction of forest response to alternative future climate scenarios. An additional component of this research involves the reconstruction of historical temperatures in the southern portion of the Rocky Mountain ecoregion using chronologies of radial growth from several high elevation tree species occurring in northern Colorado and southern Wyoming. Historical temperatures have been reconstructed for northern portions of the Rocky Mountain ecoregion. A comparable reconstruction for the southern portion of the region has not been developed. Global climate models predict that parts of the Rockies may experience future climates with no previous analogs. Historical temperature reconstructions based on proxy indicators will provide historical context for both modern climate variation and simulations of future conditions.